NILAI DASAR DAN MORALITAS KEPEMIMPINAN PENDIDIKAN ISLAM - Rusnadi Rusnadi; Hafidhah Hafidhah (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2019)
This paper is made to explain the nature of Islamic educational leadership. In Islamic education institutions are required leaders who have a fendamental value, morality and ideal characteristics. This paper uses a method of library research with a qualitative approach. Once it is known that the fundamental value a leader must have is to have a genuine and sincere intention to do good with a sense of responsibility and full commitment, and be able to immerse themselves with all the components that exist in the institution based on faith, science and morality. In addition, the moral of a leader must also cling to Aqidah and sharia in life because it is a major key in the advancement of Islam education. If the leader already has the basic value and moral then he will be able to become an ideal and characteristic leader as modeled by Rasulullah SAW.